MoOx-ZrO2 System: Preparation, Characterization and Catalytic Activity for Selective Oxidation of Diphenylsulfide - Puello Polo, Esneyder; I. Cabello, Carmen; Gazzoli, Delia (Current Catalysis, 2014)
MoOx-ZrO2 based catalysts were prepared by equilibrium adsorption in basic (pH 8) or in acid (pH 2) conditions with molybdenum content up to 3 wt.% (pH 8) and up to 8 wt.% (pH 2) using hydrous zirconium oxide, designated as ZrO2(383), as support. The samples were characterized by textural analysis (BET), X-ray diffraction (XRD), Raman and X-ray photoelectron (XPS) spectroscopies. The catalytic behavior was analyzed for the selective oxidation of diphenylsulfide (DPS) to diphenylsulfone (DPSO2) or diphenylsulfoxide (DPSO) using H2O2 as oxidizing agent. The results show that the pH of the contacting solution affects the uptake of the Mo species and the molecular state of the adsorbed species. Raman spectroscopy identified polymolybdate structures at pH 2 and molybdate aggregates at pH 8. XRD analysis revealed that at increasing molybdenum concentration the interaction between the supported species and the zirconia surface favored the tetragonal volume fraction of zirconia at the expense of the thermodynamically stable monoclinic phase in all series of samples. High conversion of DPS (88%) and selectivity to diphenylsulfone (DPSO2) (60%) was obtained for the pH 2 series of catalysts. These results suggest that the acid environment was the most efficient synthesis parameter leading to the formation of polymolybdates species which are considered the active phases in this reaction.
Keywords: MoOx/ZrO2